Laboratory evidence that dinotefuran, pyriproxyfen and permethrin combination abrogates Leishmania infantum transmissibility by sick dogs. Issue 1 (1st November 2021) - Bongiorno, G.; Bosco, A.; Bianchi, R.; Rinaldi, L.; Foglia Manzillo, V.; Gizzarelli, M.; Maurelli, M. P.; Giaquinto, D.; El Houda Ben Fayala, N.; Varloud, M.; Crippa, A.; Oliva, G.; et al.
Abstract: Dogs are reservoir hosts of leishmaniasis caused by Leishmania infantum and transmitted by phlebotomine vectors. The effect of dinotefuran, pyriproxyfen and permethrin spot‐on solution (Vectra®3D, Ceva Santé Animale, Libourne, France) on Leishmania transmissibility by naturally infected dogs via reared Phlebotomus perniciosus, was assessed. Dogs affected by leishmaniasis were submitted to xenodiagnosis and 6 infecting >10% of insects were treated topically on day 0. Antifeeding, insecticidal and anti‐transmissibility effects were evaluated through xenodiagnoses performed on days 1, 7 and 28, using individual pre‐treatment parameters as control. Feeding and mortality rates were assessed at 24 h, whereas promastigote infection, maturation and burden were assessed up to 96 h post blood meal (potentially infectious rate). On day 1, the anti‐feeding efficacy was >95% in 4 dogs, insecticidal efficacy 100% in 4 dogs, and anti‐transmissibility effect 100% in 6 dogs. Efficacy rates recorded on day 7 were very similar to day 1. On day 28, anti‐feeding and insecticidal efficacy values were much broader, ranging 32.6–100% and 7.7–94.4%, respectively. Potentially infectious insects were recorded from two dogs, with sharp decrease in transmissibility rate as compared with pre‐treatment condition. Altogether, Vectra®3D abrogated by >98% the potential Leishmania transmissibility by the examined pool of infected dogs over 1 month. Abstract : The effect of dinotefuran, pyriproxyfen and permethrin spot‐on solution (Vectra®3D) on Leishmania infantum transmissibility by naturally sick dogs via reared Phlebotomus perniciosus, was assessed. Six dogs submitted to xenodiagnosis and infecting >10% of sand fly females were treated on day 0; anti‐transmissibility effects were evaluated again by xenodiagnosis on days 1, 7 and 28. A few potentially infectious insects were recorded from two dogs on day 28. Vectra®3D abrogated by >98% the potential Leishmania transmissibility by the examined sick dogs over one month.